2022
DOI: 10.15420/ecr.2021.33
|View full text |Cite
|
Sign up to set email alerts
|

Management of Heart Failure in Patients with Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is increasingly prevalent in patients with heart failure (HF) and HF is one of the leading causes of hospitalisation, morbidity and mortality in patients with impaired renal function. Currently, there is strong evidence to support the symptomatic and prognostic benefits of β-blockers, renin–angiotensin–aldosterone inhibitors (RAASis), angiotensin receptor-neprilysin inhibitors (ARNIs) and mineralocorticoid receptor antagonists (MRA) in patients with HF and CKD stages 1–3. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…The heart and kidneys play important roles in maintaining fluid homeostasis and normal blood pressure. Heart failure progresses and persists with CKD through reduced renal blood flow, renal hemodynamic impairment, and ischemic injury [23,24]. In our study, heart failure increased the risk of CKD only in women (HR 1.24, men 1.06 (no statistical significance), women 1.44).…”
Section: Discussionmentioning
confidence: 46%
“…The heart and kidneys play important roles in maintaining fluid homeostasis and normal blood pressure. Heart failure progresses and persists with CKD through reduced renal blood flow, renal hemodynamic impairment, and ischemic injury [23,24]. In our study, heart failure increased the risk of CKD only in women (HR 1.24, men 1.06 (no statistical significance), women 1.44).…”
Section: Discussionmentioning
confidence: 46%
“…(35) Diabetes is a risk factor for substantial HF progression (16,36), and separately a population-based study in COPD patients demonstrated an increased risk of cardiovascular mortality with type II diabetes. (37) Impaired renal hemodynamics and activation of the renin-angiotensin-aldosterone system (RAAS) can lead to HF, (38) and separately reduced kidney function is associated with future HF. (39) Our findings for cardiovascular medications indicate a certain treatment profile in primary care, leading up to the post-exacerbation HF hospitalization.…”
Section: Heart Failurementioning
confidence: 99%
“…The aldosterone-stimulated volume retention exacerbates myocardial stretching and increases demands on the already failing heart. In response to myocyte distention, natriuretic peptides are released [ 35 , 38 ]. Additionally, chronic kidney hypoperfusion predisposes patients to CKD and worsens hypertension, diabetic nephropathy, and metabolic derangements, including anemia and uremia, all of which have poor prognostic outcomes [ 26 , 38 ].…”
Section: Reviewmentioning
confidence: 99%
“…In response to myocyte distention, natriuretic peptides are released [ 35 , 38 ]. Additionally, chronic kidney hypoperfusion predisposes patients to CKD and worsens hypertension, diabetic nephropathy, and metabolic derangements, including anemia and uremia, all of which have poor prognostic outcomes [ 26 , 38 ]. With the United States' growing elderly population and increases in medical advancements, it is believed that by 2030, more than eight million people will be diagnosed with HF [ 39 ].…”
Section: Reviewmentioning
confidence: 99%